Evaluation of cell behavior on modified polypropylene with swift heavy ion irradiation - Arbeitman, Claudia Roxana (2012)
Ion beam irradiation is a well known means to change the physico-chemical properties of polymers, and induced bio and citocompatibility in controlled conditions and in selected areas of surface. However, the enhancement of cell adhesion on a modified substrate does not mean that the surface is adequate for functional cells. The purpose of the present work is to study proliferation, changes in cytoskeleton and cell morphology on substrates as a function of irradiation parameters. We irradiated polypropylene with sulfur (S) ion-beam at energies of 110 MeV with fluences between 1 × 106 and 2 × 1010 ions cm−2. NIH 3T3 cells were cultured on each sample. Cell morphology was observed using phase contrast microscopy and cytoskeleton proteins with fluorescence microscopy. The analysis show different cellular responses as a functions of irradiation parameter, strongly suggests that different underlying substratum can result in distinct types of cytoskeleton reorganization.